IMPROVEMENT OF THE MECHANISM OF ORGANIZATION OF PUBLIC PROCUREMENT IN BUDGETARY ORGANIZATIONS - Ashurova N.M. (Scholars Digest Publishing, 2023)
The article discusses the improvement of the mechanism of organization of public procurement in budgetary organizations. Public procurement is a structural tool of the budget. Public procurement is literally important in terms of its tasks and functions, creating the necessary conditions for economic development.
Keywords: Public procurement, targeted programs, digital economy, customer.